PENGARUH PENGGUNAAN BETON FLY SLAB PADA GEDUNG BERTINGKAT (STUDI KASUS GEDUNG TELKOMSEL SEMARANG) - Afdholi Afdholi; Jumani Arso; Nuroji Nuroji; Hadi Wibowo (Jurnal Karya Teknik Sipil, 2013)
Telkomsel building structure is located in Jl. Pahlawan Semarang, the buildings was built using conventional reinforced concrete and then replanned using Fly Slab, where the structure of the building was designed by ”Indonesian Concrete Code (SNI03-2847-2002)”, while the analysis of earthquake load uses response spectrum method based on “ Indonesian Seismic Code ( SNI03-1726-2010)”. Fly Slab has been often used in engineering structures, from several studies Fly Slab able to provide good structural performance and more effective in increasing the loading capacity, economical advantages and accelerate the implementation of the work during the process. Fly Slab is a concrete slab with reinforcement in design with high quality technology to produce concrete which is much more effective, efficient and economical than conventional concrete. Structural analyzis calculated with the help of structural analysis program SAP2000 v10. From the results of the calculations it shown that the structural elements of the building was safe analyticaly.